IMPLEMENTASI PELAYANAN ADMINISTRASI ONLINE MENGGUNAKAN GOOGLE DRIVE UNTUK MENINGKATKAN KEPUASAN MASYARAKAT PADA KANTOR DESA PASIRHALANG - Firmansyah, Fiqri; Firdaus, Nunu Mahmud (IKIP Siliwangi, 2025)
Villages or sub-districts play an important role in the Indonesian government structure, being responsible for government affairs and the welfare of local communities. Improving administrative services, including online services, is the main focus in efforts to modernize village government. The Mixed Methods Sequential Exploratory Design research method was used to explore the implementation and impact of online administration services on community satisfaction in Pasirhalang Village. The data processing procedure starts from qualitative data and continues with quantitative data. Although there are still challenges such a lack of technological awareness, the research results demonstrate that the usage of technology, such as Google Forms, has boosted service efficiency. Solutions to overcome this challenge include inclusive approaches, training and further outreach to increase society's digital literacy. Online administration services using Google Drive have a significant positive effect on people's satisfaction. Regression analysis shows that every 1% increase in online service quality contributes to an increase in satisfaction of 0.545.